Evaluation of Differential Diagnostics Potential of Uniform Data Set 2 Neuropsychology Battery Using Alzheimer's Disease Biomarkers - Čihák, Martin; Horáková, Hana; Vyhnálek, Martin; Veverová, Kateřina; Matušková, Veronika; Laczó, Jan; Hort, Jakub; Nikolai, Tomáš (Archives of clinical neuropsychology, 2024)
OBJECTIVE: This study aims to evaluate the efficacy of the Uniform Data Set (UDS) 2 battery in distinguishing between individuals with mild cognitive impairment (MCI) attributable to Alzheimer's disease (MCI-AD) and those with MCI due to other causes (MCI-nonAD), based on contemporary AT(N) biomarker criteria. Despite the implementation of the novel UDS 3 battery, the UDS 2 battery is still used in several non-English-speaking countries. METHODS: We employed a cross-sectional design. A total of 113 Czech participants with MCI underwent a comprehensive diagnostic assessment, including cerebrospinal fluid biomarker evaluation, resulting in two groups: 45 individuals with prodromal AD (A+T+) and 68 participants with non-Alzheimer's pathological changes or normal AD biomarkers (A-). Multivariable logistic regression analyses were employed with neuropsychological test scores and demographic variables as predictors and AD status as an outcome. Model 1 included UDS 2 scores that differed between AD and non-AD groups (Logical Memory delayed recall), Model 2 employed also Letter Fluency and Rey's Auditory Verbal Learning Test (RAVLT). The two models were compared using area under the receiver operating characteristic curves. We also created separate logistic regression models for each of the UDS 2 scores. RESULTS: Worse performance in delayed recall of Logical Memory significantly predicted the presence of positive AD biomarkers. In addition, the inclusion of Letter Fluency RAVLT into the model significantly enhanced its discriminative capacity. CONCLUSION: Our findings demonstrate that using Letter Fluency and RAVLT alongside the UDS 2 battery can enhance its potential for differential diagnostics.
Keywords: Mild cognitive impairment; Assessment; diferenciální diagnóza; Female; Cognitive Dysfunction; biologické markery; Amyloid beta-Peptides; Neuropsychological Tests; tau Proteins; Biomarkers; ženské pohlaví; průřezové studie; neuropsychologické testy; lidé; amyloidní beta-protein; Aged, 80 and over; Diagnosis, Differential; Cross-Sectional Studies; Male; Alzheimer’s disease; Aged; Alzheimer Disease; kognitivní dysfunkce; Alzheimerova nemoc; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; proteiny tau; Humans